π-prismands: flexible hosts for metal ions - Kunze, Andreas; Balalaie, Saeed; Gleiter, Rolf; Rominger, Frank (European journal of organic chemistry, 2006)
The π-prismands dealt with in this paper are: 1,8-diazabicyclo[6.6.6]eicosa-4,11,17-triyne (6), 1,8-diazabicyclo[6.6.5]nonadeca-4,11-diyne (7), 1,8-diazabicyclo[6.6.6]eicosa-4,11-diyne (8), 1,10-diazabicyclo[8.6.6]docosa-5,13,19-triyne (9), 17-(1,4)benzena-1,8-diazabicyclo[6.6.5]nonadecaphane-4,11-diyne (10), 11,16-(1,4)dibenzena-1,8-diazabicyclo[6.5.5]octadecaphane-4-yne (11) and 4,10,15-(1,4)tribenzena-1,7-diazabicyclo[5.5.5]heptadecaphane (12). The synthesis of 9 is reported. The molecular parameters obtained from X-ray investigations on single crystals of 6?9 as well as of 10?12 are compared with each other. Also discussed are the structures of the monoprotonated forms of 6 and 12. The π-prismands 6?12 form stable complexes with Ag+ and Cu+. The crystal structures of the metal complexes as well as their spectroscopic properties are reported. Both reveal that the metal center interacts with the nitrogen atoms and the π-systems of the bridges.(? Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2006)